Comprehensive study on the pyrolysis product characteristics of tobacco stems based on a novel nitrogen-enriched pyrolysis method. (1st March 2022) - Bai, Jing; Gao, Hang; Xu, Junhao; Li, Lefei; Zheng, Peng; Li, Pan; Song, Jiande; Chang, Chun; Pang, Shusheng
Abstract: The research on tobacco stems (TS) mainly focuses on the analysis of their own pyrolysis products, and there are few reports on the nitrogen-enriched pyrolysis of TS. Therefore, the microwave pyrolysis characteristics of TS impregnated with different ammonia sources was investigated. The yield, composition and characteristics of pyrolysis products were investigated by elemental analysis, GC/MS, GC and XPS, and the pyrolytic mechanism of TS was discussed. The results showed that TS impregnated with ammonia sources increased the contents of nitrogen-containing compounds (NCCs), and the contents of acid and carbonyl compounds decreased. The introduction of glycine inhibited the pyrolysis of TS to some extent and improved the yield of solid products. Among them, the bio-oil of TS loaded with 6 wt% urea had the highest content of NCCs (33.469%), which were mainly nitrogen-containing heterocyclic compounds (NCHs), including pyridines, pyrroles and pyrazines. Moreover, the introduction of urea inhibited the decomposition of nicotine and improved the yield of this valuable chemical. Biochar is widely applied in fertilizer, catalyst, electrode material and adsorption material because of its high N content. The impregnation of urea increased the yield of H2 and lowered the yield of CO2 . Moreover, the nitrogen-rich pyrolysis of biomass increases the content of NCCs and improves the useable value of products. Highlights: TS were pretreated by impregnating different ammonia sources before microwave pyrolysis. The carbonyls were transformed into nitrogen-containing compounds (NCCs) through the Maillard reaction. The contents of NCCs and phenols in 6UAL were the highest, and the pyridine quantity was increased remarkably. The mechanism for the formation of NCCs was proposed in microwave pyrolysis process.